Research on Analysis and Recognition of Car User Portrait based on Big Data of Vehicle Network - Pang, Jinxi; Lu, Jin (International Journal of Computer Science and Information Technology, 2025)
With the rapid development of vehicle networking technology, big data of vehicle networking has become one of the core resources of intelligent transportation system. As the key technology of the application of big data in the networking of vehicles, the analysis and identification of user portraits play an important role in realizing the landing of user portraits and precise advertising, improving the efficiency of traffic management, ensuring driving safety and optimizing the user experience. This paper aims to explore the research on user portrait analysis and recognition based on vehicle network big data, and realize the accurate identification of user portrait through comprehensive analysis of vehicle driving data, user behavior characteristics and other information. First of all, the basic data fields of the big data of the Internet of vehicles are introduced, and then the data is structured, including data preprocessing, feature extraction, feature recombination, and finally the unsupervised model K-Means++ is used for model construction. Through experimental verification, the method proposed in this paper has achieved good results in the recognition and analysis of user portrait, and can realize the landing of user portrait and precise advertisement delivery scene, which has high practical application value.